CONSTRUIREA SPAŢIULUI EDUCAŢIONAL - COMPONENTĂ A MANAGEMENTULUI PROCESULUI EDUCAŢIONAL - USM ADMIN (Moldova State University, 2009)
The educational environment is focused mainly on the space organization. Rooted in the primary relation between man and space, the educational space was considered as important by different directions inside the active school. In our days, the Whole Language Approach offers perhaps the only clear and focused systematization of the classroom space for educational goals.